Concrete Diversity Initiatives in Political Science: A Faculty Workload Intervention Program. - Stoll, Heather; McLaughlin-Zamora, Michele; Anderson, Sarah E. (PS: Political Science & Politics, 2023)
The article focuses o the faculty workload intervention program based on the Faculty Workloads and Rewards Project (FWRP) including work activity area of mentoring, and mentions implementation of the program at the University of California, Santa Barbara.